Income Inequality and Noncash Food Assistance Program in Central Java Province - Yusuf Munandar (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2021)
One measure of income inequality that is often used is the Gini Coefficient. In Central Java Province, the income inequality in March 2019 was increasing compared to income inequality in September 2018. To reduce this income inequality, the government is focusing on increasing government spending in the field of social assistance, including Non-Cash Food Assistance (Bantuan Pangan Non Tunai/BPNT). Thus, this study aims to calculate and obtain a reduction in the Gini Coefficient as a result of the implementation of the BPNT program in the Central Java Province of Indonesia. This study uses the Counter Factual Analysis (CFA) method and the March 2019 Susenas data. This study concludes that the implementation of the BPNT program in 2019 is quite effective in reducing the level of income inequality in the Central Java Province of Indonesia, which is able to reduce the Gini Coefficient of Central Java Province by -1.20%. The implementation of the BPNT program was able to make the expenditure of the lower class population increase faster than the expenditure of upper and middle class population. The implementation of the BPNT program changes the map of the income inequality level of 35 districts/cities in the Central Java Province of Indonesia but does not change the map of the level of income inequality between urban and rural areas in the Central Java Province of Indonesia. In addition, the implementation of the BPNT program in the Central Java Province of Indonesia has not been able to change the category of income inequality in the Central Java Province of Indonesia, namely that it remains in the moderate category. This study recommends improvements in terms of the target recipients of BPNT, the quality of the human resources of the companions, the time for receiving assistance, the quality of rice, and the readiness of e-warong in 35 districts/cities in the Province of Central Java, Indonesia.